If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18y + 4 = 70 Reorder the terms: 4 + 18y = 70 Solving 4 + 18y = 70 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 18y = 70 + -4 Combine like terms: 4 + -4 = 0 0 + 18y = 70 + -4 18y = 70 + -4 Combine like terms: 70 + -4 = 66 18y = 66 Divide each side by '18'. y = 3.666666667 Simplifying y = 3.666666667
| (9x^8yz^6)(6x^7z)= | | 4f-12=0 | | x-16=2x-14 | | 4x^4(-6x^5-7)= | | -x-3=x-19 | | 2x-15=x-21 | | 7x-14=-49 | | 6x+79=10x-9 | | 2x+9=-2x+29 | | 11=4-2x | | -0.3x+6=-0.5x+9 | | -0.3+6=-0.5+9 | | x+3=-2x-18 | | -3x+16=x+32 | | 2b^2-7b+6=0 | | (-4x^7)(6)= | | 5x-12=6x-18 | | 11x-15=4x-50 | | 2x+19=39 | | 5x+9=6x+13 | | -2x+17=-1 | | -x-1=-5x+27 | | 5x-14=-49 | | 3x-5=-2x-25 | | -x-1=-5x-25 | | -2x-3=-5x-9 | | 60x-180=5x^2 | | (2x^7)(9)= | | x^4+x^3-8x+8=0 | | (2y-5)(2y-5)= | | 4+14p-2=9p+72-5p | | -47=7+9x |